Central Nervous System Systemic Lupus Erythematosus (CNS-SLE) Vasculitis Mimicking Lewy Body Dementia: A Case Report Emphasizing the Role of Imaging With an Analysis of 33 Comparable Cases From the Scientific Literature. (March 2021) - Abraham, Peter; Neel, Ian; Bishay, Steven; Sewell, Daniel D.
Introduction: Neuropsychiatric symptoms occur in 30% to 40% of patients living with systemic lupus erythematosus (SLE). Brain imaging may play a pivotal role in determining the etiology as it did for the case presented here. Methods: A new case of central nervous system (CNS) SLE is presented along with an analysis of 33 comparable cases from the scientific literature. Results: A 70-year-old female with subacute cutaneous lupus presented to a university-based geropsychiatry program after 1 year of benign visual hallucinations and several months of shuffling gait, recurrent falls, and forgetfulness. These symptoms were highly suggestive of Lewy body dementia; however, the patient's history of basal ganglia infarct, cognitive testing demonstrating inattention and executive dysfunction, and follow-up brain imaging, which did not reveal acute findings, aligned with cerebral pathology previously attributed to vasculitis and supported the diagnosis of subcortical dementia due to SLE-CNS vasculitis. Oral prednisone 20 mg daily resolved her symptoms. Over the next 19 months, her prednisone was tapered completely and her symptoms did not return. A systematic literature search identified 33 comparable cases. Conclusion: An analysis of previously published cases suggests that extending the duration of the prednisone taper beyond 1 year may decrease the risk of later occurring neuropsychiatric symptoms in this patient population.